2012
DOI: 10.1209/0295-5075/97/43001
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-long-range giant dipole molecules in crossed electric and magnetic fields

Abstract: We show the existence of ultra-long-range giant dipole molecules formed by a neutral alkali ground state atom that is bound to the decentered electronic wave function of a giant dipole atom. The adiabatic potential surfaces emerging from the interaction of the ground state atom with the giant dipole electron posses a rich topology depending on the degree of electronic excitation. Binding energies and the vibrational motion in the energetically lowest surfaces are analyzed by means of perturbation theory and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 35 publications
3
28
0
Order By: Relevance
“…The GD ground-state PES is deformed from a Gaussian to a broader parabolic shape, which has also been reported in Ref. [27]. Varying the included excited states reveals that these shifts originate from a coupling to higher z-excited states with the same parity.…”
Section: Potential Energy Surfacessupporting
confidence: 79%
See 2 more Smart Citations
“…The GD ground-state PES is deformed from a Gaussian to a broader parabolic shape, which has also been reported in Ref. [27]. Varying the included excited states reveals that these shifts originate from a coupling to higher z-excited states with the same parity.…”
Section: Potential Energy Surfacessupporting
confidence: 79%
“…Therefore, a pure triplet eigenstate of H spin does not couple to any other spin state, and both triplet states can be diagonalized independently, providing a route for direct comparison with Ref. [27]. In contrast, the two mixed-character spin states |+1/2| ↑↓ and |+1/2| ↓↑ are strongly coupled by P 1 and have to be considered simultaneously, resulting in 2×1891 = 3782 basis states necessary for diagonalization.…”
Section: The Corresponding Eigenenergies Serve As Potential Energy Sumentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the usual Rydberg states, giant-dipole states are of decentered character with an electron-ionic core separation up to several micrometers, leading to huge permanent electric dipole moments in the range of hundreds of thousand Debye. Applications to matter-antimatter atoms have predicted bound state lifetimes of many years, and recent studies have indicated the existence of diatomic ultra-long ranged giant-dipole molecules [29].…”
Section: Introductionmentioning
confidence: 99%
“…These molecules should therefore be somewhat more tightly bound than those predicted for rubidium [1,23]. The permanent electron dipole moments associated with these molecules are in the kdebye range, allowing for the possibility of delicate manipulation of these molecules with electric and magnetic fields [30,31]. The stability of these states is limited by black body radiation [17], with an estimated lifetime of a few µs.…”
Section: Matthew T Eiles and Chris H Greenementioning
confidence: 98%